A Tale of Two Sociologies: Analyzing Versus Critique in UK Sociology. (December 2017) - Williams, Malcolm; Sloan, Luke; Brookfield, Charlotte
Several studies, in recent years, have demonstrated what has become known as the 'quantitative deficit' in UK sociology. This deficit is primarily manifested through negative student attitudes towards quantitative methods, a lack of ability in that area and a paucity of quantitative research and publication in the discipline that utilises quantitative methods. While we acknowledge the existence of that deficit, we argue in this article, and present some initial evidence in support of this argument, that the issue is not simply just about a 'crisis of number' but the kind of sociology taught and practised in the United Kingdom. We suggest here that there are two broad categories of sociology that do not necessarily divide along quantitative–qualitative lines, which we term 'analytic' and 'critique'. Much of UK sociology takes a 'critique' approach, which may well be a quite legitimate way to do sociology, but is not a sufficient basis on which quantitative sociology can be done and has implications for the future of the discipline.